THE DELIBERATIVE GOVERNANCE IN LABOUR POLICY INNOVATION - Tasroh; Paulus Israwan Setyoko (Lembaga Penelitian Universitas Pasundan, 2025)
Abstract This study aims to analyse and examine how global value of deliberative governance of labour policies in Banyumas local government operates with a cultural heritage. By descriptive methods through in-depth interviews, policy studies, and observations of 100 relevant key-informants, it can be concluded that labour policy deliberations are not yet fully deliberative. Otherwise, labour policy deliberations held by non-governmental organizations are actually more deliberative. Among other things, this is due to the more free, open, democratic and autonomous interaction patterns and communication flows held by non-governmental organizations. The next factor is due to the fact that the selection of policy deliberation actors has not been carried out through random selection, the discussion agenda has not discussed labour protection issues comprehensively, the supervision of post-policy deliberation proposals at the district level is very difficult to do, and the participation employers is still at the level of pseudo-participation. Based on these conditions, efforts need to be made starting from the expansion of new public spaces, increasing the deliberation budget, selection of actors based on competence and authority, dissemination, more massive information dissemination of the labour protection policy agenda, and the intensity of labour and employer meetings so that industrial relations in the labour protection agenda can run dynamically and be able to realize an increase in the number of protected workers. With policy deliberation, it is expected that a new consensus will be enhanced in order to prevent conflicts of labour more early. Keywords: Policy Innovation, Manpower Development, Deliberative Governance